Nourishing diversity: exploring the relationship between food variety and anemia status among women workers. - Haya, Miratul; Farida Baliwati, Yayuk; Khomsan, Ali; Briawan, Dodik (Nutrición Clínica y Dietética Hospitalaria, 2025)
Introduction: Anemia in working women is a significant health issue as it can reduce productivity, concentration and well-being. High workload, unbalanced food consumption patterns, and limited access to sources of iron and other mi cronutrients increase the risk of anemia. Objective: This study aims to analyze food diversity re lated to the type and amount of food consumed by anemic and non-anemic women workers. Method: This study used a cross-sectional design involving 140 women workers in rubber plantations in Seluma Regency, Bengkulu Province, Indonesia. Samples were taken using stratified random sampling technique. Anemia status was determined through biochemical examination and food consumption data was collected through 24-hour food recall method and minimum dietary diversity for women (MDD-W) indicator. The relationship between variables was analyzed using the correlation test. Results: The prevalence of anemia among women work ers was 35%, women workers with primary education had a higher prevalence of anemia (71.4%) compared to those with secondary education (18.1%). In the lowest income quintile the prevalence of anemia reached 42.9%, while in the high est income quintile it was only 20.6%. Women workers with out anemia had better food consumption diversity (73.9%) than the anemia group (26.1%). Conclusion: Education level, income and diverse food con sumption had a significant relationship with anemia status. Consumption of tempeh, chicken liver, sardines and green leafy vegetables such as moss, moringa and melinjo leaves support iron sufficiency and play a role in preventing anemia.